Evaluation of Development Programs : Randomized Controlled Trials or Regressions? - Elbers, Chris (Oxford University Press on behalf of the World Bank, 2016)
Can project evaluation methods be used to evaluate programs: complex interventions involving multiple activities? A program evaluation cannot be based simply on separate evaluations of its components if interactions between the activities are important. In this paper a measure is proposed, the total program effect (TPE), which is an extension of the average treatment effect on the treated (ATET). It explicitly takes into account that in the real world (with heterogeneous treatment effects) individual treatment effects and program assignment are often correlated. The TPE can also deal with the common situation in which such a correlation is the result of decisions on (intended) program participation not being taken centrally. In this context RCTs are less suitable even for the simplest interventions. The TPE can be estimated by applying regression techniques to observational data from a representative sample from the targeted population. The approach is illustrated with an evaluation of a health insurance program in Vietnam.